Service Quality and Customer Satisfaction in the Post Pandemic World: A Study of Saudi Auto Care Industry - Zygiaris, Sotirios; Hameed, Zahid; Ayidh Alsubaie, Mubarak; Ur Rehman, Shafiq (Frontiers in Psychology, 2022)
The aim of this research is to examine the impact of service quality on customer satisfaction in the post pandemic world in auto care industry. The car care vendor in the study made effective use of social media to provide responsive updates to the customers in the post pandemic world, such use of social media provides bases for service quality and customer satisfaction. The study examined the relationship between service quality and customer satisfaction using the SERVQUAL framework. According to the findings, empathy, reliability, assurance, responsiveness, and tangibles have a significant positive relationship with customer satisfaction. Our findings suggest that it is critical for workshops to recognize the service quality factors that contribute to customer satisfaction. Findings also suggest that empathy, assurance, reliability, responsiveness, and tangibles contribute to customer satisfaction. Auto repair industry must regularly provide personal attention, greet customers in a friendly manner, deliver cars after services, notify customers when additional repairs are required, and take the time to clarify problems to customers. Furthermore, workshops must screen and hire courteous staff, that can clearly communicate the services required to customers both in-person and online, and effectively communicate the risks associated with repairs. Service quality seems to be aided by prompt services.